(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
This paper is aimed to study the Agricultural activities of the Malayali Tribal for Subsistence and Economic needs in the mid elevation forest of Pachamalai Hills, Eastern Ghats, Tamil nadu. About 8 percent of the Indian population belongs to a category listed as Scheduled Tribes enumerated in the Schedule to Article 342 of the Constitution of India. Tribal people has been seen to be strongly associated with the forests, hills and remote areas, practicing a unique life style, having a unique set of cultural and religious beliefs. For millennia, tribal communities have lived in forests and survived on hunting and gathering. However, with growing population and resource pressure, it is now witnessing that a rise in livelihoods based on settled farming. In the study area, cereals are the major crop cultivated for their edible grains. The tribal people living in the hills tops of the study area were cultivated 11 major agricultural crops. They are, Eleusine coracana, Panicum miliare, Oryza sativa (verity I) (Mara Nellu), Oryza sativa (verity II), Manihot esculenta, Macrotyloma uniflorum, Vigna mungo, Sesamum orientale, Paspalum sp, Pennisetum americanum and Setaria italica. Among them, Paspalum sp gives the maximum yield with 655 kg acre-1. DOI: http://dx.doi.org/10.3329/ijarit.v2i1.13992 Int. J. Agril. Res. Innov. & Tech. 2 (1): 32-36, June, 2012